The role of training and hyperbaria in the rehabilitation process after crushing injury of the sciatic nerve in mice - assessment of functional parameters using the CATWALK XT platform - Anna Dolińska; Dariusz Górka; Michał Trzęsicki; Natalia Białoń; Mikołaj Górka (Kazimierz Wielki University, 2023)
Introduction Peripheral nerve injuries are one of the most common injuries in the population and affect 3% of trauma patients. Unfortunately, full functional regeneration is a relatively rare phenomenon. Attempts to heal and regenerate damaged nerves are a frequent subject of research, especially when animal models are considered, and the results are not always satisfactory Aim of the study The aim of this study was to evaluate functional regeneration after sciatic nerve damage in mice treated with hyperbaric oxygen therapy and locomotor training, and to check the effectiveness of these methods. Materials and Methods The research material consisted of 75 mice with a damaged sciatic nerve. The mice were divided into three groups: H- subjected to hyperbaric therapy, T- subjected to training and K- not subjected to any therapy (control group). A functional gait analysis was performed using the CATWALK XT gait platform based on selected gait parameters. Results In the groups subjected to both hyperbaric therapy and training, the results of the analysis showed faster functional recovery. Statistically significant differences in the print area, print length, swing and SFI parameters were noted in the treated groups as opposed to the control group, while in the hyperbaric group of mice functional recovery turned out to be the most effective and fastest. Conclusion Mice of both groups (H, T) showed a faster recovery of sensory and motor functions in contrast to the control group not subjected to any treatment.